Peran PAK dalam Menghadapi Distraksi Short Video terhadap Konsentrasi Mengerjakan Tugas bagi Kalangan Pelajar Kristen - Junardi Sihaloho; Donny Ardo Eka Dharma Putra Walui (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
The development of the current era is characterized by increasingly advanced technology that makes humans live in an instant. Of course, apart from the positive impact, there must be a negative impact produced through the development of technology, one of which is the distraction of short videos on the concentration of doing assignments for students, especially Christians. The purpose of this study is how or what is the role of Christian religious education to be able to handle Christian students who experience short video distraction which makes it difficult to concentrate on doing academic assignments. Through research with literature analysis with a qualitative approach, it was found that the role of Christian religious education in dealing with the distraction of short videos on concentration on assignments for Christian students is first, to bring students closer to God through worship so that they love God and hear the voice of truth. Second, providing an understanding of the awareness of the dangers of short videos on learning concentration. Third, controlling students to divide their time between doing assignments and watching short videos. Fourth, the awareness that students have does not stop at themselves but results in sharing with other students so that they experience change together. These roles will be able to be carried out if accompanied by examples or examples from Christian religious education teachers and lecturers who have finished with short video addiction, so that the students will be able to change their behavior together. These roles can only be fulfilled if accompanied by the example of a Christian education teacher or lecturer who has overcome addiction to short videos, so that students can find a good role model.